REGENERASI TANAMAN DARI JARINGAN KOTILEDON +RUAS BENIH KEDELAI, {Glycine max L., KULTIVAR WILIS) DENGAN RADIASI SINAR GAMMA [Plant Regeneration from Cotyledons of Mature Soybean ( Glycine max L. Wilis Cultivar Using Gamma Rays] - Hutabarat, Dameria; Ratma, Rivaie (BERITA BIOLOGI, 1999)
Soybean Wilis cultivar was efficiently regenerated in vitro via somatic embryogenesis. Cotyledonary explants were excised from mature geminating seeds. Seeds were germinated on agar solution and on B5 medium enriched with 5 ppm BA, 0,25 pom IBA and 500 ppm casein hydrolyzate. Cotyledonary nodes from both germinating seeds were excised and cultured on B5 medium enriched with 5 ppm BA, 0,25 ppm IBA and 500 ppm casein hydrolyzate. Age of seedlings had a remarkable influence on shoot regeneration. Cotyledon from seeds germinated on agar solution with light gave better result in shoot regeneration compare with those germinated in darkness. The highest number of regenerants per explants (5 shoots) was produced by cotyledon from seeds germinated on 65 medium enriched with 5 PPM BA, 0,25 PPM IBA and 500 PPM casein hydrolyzate in darkness. The seeds of soybean were exposed to gamma-rays doses 10 Gy then germinated on S5 medium enriched with 5 PPM BA,0,25 PPM IBA and 500 ppmcase/n hydrolyzate did not improve the number of plant regeneration.Only 5-day-old seedlings from seeds were exposed to gamma-rays dose 30 Gy could improve the number of shoot regeneration, one of the cotyledonary node treated produced 21 regeneration shoots.